Herb gminy (wiejskiej) Zduńska Wola - Adamczewski, Marek (Biuletyn Szadkowski, 2014)
Zduńska Wola (rural) commune coat of arms was adopted in 2001. lt was designed by Andrzej Dabrowski, a designer connected with the Polish Heraldry Centre. The emblem includes reference to the controversial mid-19th century version of Zduńska Wola city crest or the region's bee-keeping tradition (three bees ), and to the Siemiątkowski family ( coat of arms Jastrzębiec) living in Zduńska Wola region in the 19th and first half of the 20th century (a horseshoe and a cross). In 2001 the project of the sign, with due explanation, was submitted, as is required by law, to the Ministry oflnternalAffairs andAdministration for opinion. The initial opinion prepared by experts from the Heraldry Committee was negative, but it did not lead to the issuing of a decision in this matter by the minister in charge of administration. The objections to the coat of arms of Zduńska Wola (rural) commune, expressed by the experts of the Heraldry Committee, and the lack of a positive ministeriał opinion, which is necessary for adoption of the emblem, indicate that in the future there may be a change of the emblem. Perhaps a good starting point for a new coat of arms should be St. Catherine, the patron saint of the church in Korczew, which also was a parish church for Zduńska Wola and other localities in its neighbourhood.